The care economy / Tim Jackson. - Jackson, Tim, 1957- (Polity, 2025)
Care is the foundation of organic life. But its fate in the economy is precarious and uncertain. The labour of care is arduous and underpaid. Yet without it health and vitality are impossible. Care itself ends up leading a curious dual life. In our hearts it's honoured as an irreducible good. But in the market it's treated as a second class citizen - barely recognised in the relentless rush for productivity and wealth. How did we arrive in this dysfunctional place? And what can we do to change things? What would it mean to take health seriously as a societal goal? What would it take to adopt care as an organising principle in the economy? Renowned ecological economist Tim Jackson sets out to tackle these questions in this timely and deeply personal book.